O Caráter Tectônico do Moderno Brasileiro: Bernardes e Campello na Paraíba (1970-1980) - Rocha, Germana Costa (2012)
This study aims to analyze the tectonic character of the works of Sergio Bernardes and Glauco Campello architects, built in Paraiba, between the turn of the decade in 1970 and early 1980 in order to bring reflections about the poetics of construction s importance in the formal structure of the architecture, contributing to the debate about the specificitiesand peculiarities of modern architecture produced in Brazil. The research, using the strategies of the case study, startsfromthe review on the use of "tectonic" by Kenneth Frampton and other scholars of the term, to base the concept and set the analytical parameters of the tectonics. Then it proceeds to the insertion of buildings in the cultural and socio-political Brazilian s context in the periodproposed forstudy, in sequence, analyzesthe works of each architect. The study confirms that the expressive power of Brazilian heroic modern architecture, emphasizing the poetics of construction, sediments a tectonic culture that resonates in the following generations